Marangoni Convection in a Wavy Trapezoidal Enclosure with Different Amplitudes - Syed Muhammad Naquib Al'Aidrus, Sharifah Nuriza; Siri, Zailan; Mohammad Zubir, Mohammad Nashrul (Malaysian NANO-An International Journal, 2022)
In this paper, Marangoni convection inside a trapezoidal enclosure with nanofluid is numerically studied for different amplitudes. One side of the cavity is heated while the other is cooled with natural convection taking place at the top wall. The fluid flow and heat transfer are investigated at different amplitudes, particle volume fractions, Rayleigh and Marangoni numbers. The results are then shown in the form of streamlines, isotherms, local Nusselt and average Nusselt numbers. It was discovered that increasing the amplitude of the heated wavy wall improved heat transfer significantly, though the strength of fluid flow diminishes slightly.